2018
DOI: 10.1016/j.ebiom.2018.10.056
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Splicing Machinery Components Influence, Precede, and Early Predict the Development of Type 2 Diabetes: From the CORDIOPREV Study

Abstract: BackgroundType-2 diabetes mellitus (T2DM) is a major health problem with increasing incidence, which severely impacts cardiovascular disease. Because T2DM is associated with altered gene expression and aberrant splicing, we hypothesized that dysregulations in splicing machinery could precede, contribute to, and predict T2DM development.MethodsA cohort of patients with cardiovascular disease (CORDIOPREV study) and without T2DM at baseline (at the inclusion of the study) was used (n = 215). We determined the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 31 publications
0
43
0
1
Order By: Relevance
“…Each year, T2DM was diagnosed according to the diagnosis criteria of ADA, specifically, if one or more of the following criteria were present in the study subjects: fasting plasma glucose (FPG) concentration ≥126 mg/dL, FPG ≥200 mg/dL after 2-h of oral glucose test (OGTT), glycated hemoglobin (HbA1c) ≥6.5% (≥48 mmol/mol). In the present study, we included the Incident-T2DM cases after a median follow-up of 60 months ( n = 107) together with 108 matched, randomly selected controls from the remaining 355 subjects who did not develop T2DM (non-T2DM subjects) during the study period, as previously reported [ 10 ] ( Supplementary Figure S1 ). The random selection of the non-T2Dm subjects was performed using stratified sampling from the 462 non-T2DM subjects of the CORDIOPREV study according to the following clinical, anthropometric and biochemical variables: diet, age, gender, fasting plasma glucose, body mass index, low-density lipoprotein (LDL)-cholesterol and high-density lipoprotein (HDL)-cholesterol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Each year, T2DM was diagnosed according to the diagnosis criteria of ADA, specifically, if one or more of the following criteria were present in the study subjects: fasting plasma glucose (FPG) concentration ≥126 mg/dL, FPG ≥200 mg/dL after 2-h of oral glucose test (OGTT), glycated hemoglobin (HbA1c) ≥6.5% (≥48 mmol/mol). In the present study, we included the Incident-T2DM cases after a median follow-up of 60 months ( n = 107) together with 108 matched, randomly selected controls from the remaining 355 subjects who did not develop T2DM (non-T2DM subjects) during the study period, as previously reported [ 10 ] ( Supplementary Figure S1 ). The random selection of the non-T2Dm subjects was performed using stratified sampling from the 462 non-T2DM subjects of the CORDIOPREV study according to the following clinical, anthropometric and biochemical variables: diet, age, gender, fasting plasma glucose, body mass index, low-density lipoprotein (LDL)-cholesterol and high-density lipoprotein (HDL)-cholesterol.…”
Section: Methodsmentioning
confidence: 99%
“…In this context, early identification of patients at higher risk of T2DM development is critical for prevention of new cardiovascular events [ 8 , 9 ]. Interestingly, in searching for novel associated molecular mechanisms and predictive markers, we recently discovered that the expression pattern of certain splicing machinery elements in the peripheral blood mononuclear cells (PBMCs) of patients is tightly associated with the risk of T2DM and could accurately predict T2DM development in those individuals from the CORDIOPREV study, outperforming the capacity of classical predictors of T2DM development, such as glycated hemoglobin (HbA1c) or predictive scores (FINDRISK) [ 10 ], two established strategies that have limitations and cannot precisely predict an individual’s risk of developing T2DM [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific primers for human transcripts including components of the major spliceosome (n = 10), minor spliceosome (n = 4), associated SFs (n = 25) and three housekeeping genes (ACTB, GAPDH and HPRT) were specifically designed with the Primer3 software and StepOne TM Real-Time PCR System software v2.3 (Applied Biosystems, Foster City, CA, USA) (Supplemental Table 1). Preamplification, exonuclease treatment and qPCR dynamic array based on microfluidic technology were implemented as recently reported [11,12], following manufacturer's instructions using the Biomark System and the Real-Time PCR Analysis Software (Fluidigm). To control for variations in the efficiency of the retro-transcription reaction, mRNA copy numbers of the different transcripts analysed were adjusted by normalization factor, calculated with the expression levels of ACTB and GAPDH using GeNorm 3.3 [13].…”
Section: Qpcr Dynamic Array Based On Microfluidic Technologymentioning
confidence: 99%
“…Significant relation between categorized mRNA expression and biochemical PCa recurrence was studied using the long-rank-p-value method. Predictive models were constructed by Random Forest algorithm (with R language) as classifier as previously reported [11,12]. The rest of the statistical analyses were assessed using GraphPad Prism 7 (GraphPad Software, La Jolla, CA) or SPSS version 17.0.…”
Section: Statistical and Bioinformatic Analysesmentioning
confidence: 99%